Pengelolaan Risiko Pada Usaha Pengolahan Kopi “Ud Princess” Di Kabupaten Pamekasan - M Ali Mashur Sidik; Elys Fauziyah (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
Risk Management In “UD Princess” Coffee Processing Business in Pamekasan Regency. UD Princess is one of the coffee processing industries in Pamekasan Regency which has good competitiveness in offering its products. However, this business has production data that end up fluctuating so that it becomes an indicator of risk and uncertainty. This study aims to identify the sources of risk, analyze the level of risk and formulate a risk control design in coffee processing at UD Princess. The data analysis method used is fishbone and Expert Opinion Approximation. The results of the study indicate that the sources of risk at UD Princesscan come from production, marketing, human resources, finance, and institutional activities.Among several sources of risk, marketing activities and human resources are the sources of risk that have the greatest level of risk. Design strategies that can be used to control risk in UD Princess is mitigation and preventive strategy.